Oral traditions as a fount of ethnomathematical knowledge: A bibliometric analysis of contemporary research trends - Nugraha, Adhi Surya; Nugraha, Danang Satria (IKIP Siliwangi and I-MES, 2025)
This study mapped the contemporary research landscape surrounding “oral traditions as a fount of ethnomathematics knowledge” through a bibliometric analysis employed as a methodological procedure. The main problem addressed in this study is the lack of a comprehensive consideration of evolving research trends and intellectual structure within ethnomathematics, i.e., the role of oral traditions as a source of knowledge. Oral traditions, defined as the cultural knowledge, art, ideas, and practices transmitted verbally across generations, offer a rich repository of ethnomathematical insights. 713 publications were identified from the Dimensions database between 2014 and 2024. This bibliometric analysis focused on identifying key research themes, authors, publishers, keywords, or key terms distributions within the corpus of extracted publications, as well as temporal trends in publication activity and citation patterns. The findings revealed a growing interest in the field, focusing on (a) educational context, (b) cultural studies, and (c) the intersection of mathematics and language. The analysis also identified key research themes, such as (a) the role of language and culture in shaping mathematical thought, (b) the development of ethnomathematical practices, and (c) the pedagogical implications of incorporating ethnomathematics into formal education. Additionally, 11 influential scholars who are driving the field forward were identified. According to the term distribution analysis, of the 6,092 terms, 316 met the threshold (minimum number of occurrences of the term: 6). For each 316 terms, a relevance score has been calculated. Based on this score, the most relevant terms have been selected. The VOSviewer’s default setting (60% of the most relevant terms) resulted in selecting 190 terms. Based on the given criteria, there is a result of 5 distinctive clusters related to the query that emerged. This study provides theoretical insights into the conceptual foundations of ethnomathematics derived from oral traditions and empirical evidence for informing future research directions and pedagogical practices in mathematics education.